Evaluatıon Of Lower Thırd Molars From An Orthodontıc Poınt Of Vıew - Aslı Ender Telli (Galenos Yayinevi, 1996)
In this article, the lower third molar teeth is evaluated under the headings: the development of lower third molars, space preparation in the dental arch before lower third molar eruption, causes of lower third molar impaction, prediction methods of lower third molar impaction, the views about to extract or keep the lower third molars in the mouth, influence of anterior tooth extraction to the lower third molar eruption, the relationship of lower anterior crowding and the lower third molar eruption.